2022
DOI: 10.3389/fimmu.2022.959733
|View full text |Cite
|
Sign up to set email alerts
|

Not enough by half: NFAT5 haploinsufficiency in two patients with Epstein-Barr virus susceptibility

Abstract: IntroductionThe transcription factor Nuclear factor of activated T cells 5 (NFAT5), pivotal in immune regulation and function, can be induced by osmotic stress and tonicity-independent signals.ObjectiveWe aimed to investigate and characterize two unrelated patients with Epstein-Barr virus susceptibility and no known genetic etiology.MethodsAfter informed consent, we reviewed the electronic charts, extracted genomic DNA, performed whole-exome sequencing, filtered, and prioritized their variants, and confirmed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Similarly, it has been reported that NFAT5 inhibits CVB3 replication partially via enhancing expression of inducible nitric oxide synthase (iNOS) ( 29 ), providing a sample that supports our speculations. Interestingly, when starting to prepare our manuscript, one paper was published, which reported that NFAT5 haploinsufficiency may potentially correlate with Epstein-Barr virus (EBV, also called human gammaherpesvirus 4) susceptibility as observed in two patients ( 18 ), indicating that NFAT5 may restrict EBV infection in vivo , as observed in BoHV-1 productive infection in vitro . Together with these reports, antiviral effects of NFAT5 may universally apply to broad spectrum of viruses, including herpesvirus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it has been reported that NFAT5 inhibits CVB3 replication partially via enhancing expression of inducible nitric oxide synthase (iNOS) ( 29 ), providing a sample that supports our speculations. Interestingly, when starting to prepare our manuscript, one paper was published, which reported that NFAT5 haploinsufficiency may potentially correlate with Epstein-Barr virus (EBV, also called human gammaherpesvirus 4) susceptibility as observed in two patients ( 18 ), indicating that NFAT5 may restrict EBV infection in vivo , as observed in BoHV-1 productive infection in vitro . Together with these reports, antiviral effects of NFAT5 may universally apply to broad spectrum of viruses, including herpesvirus.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies indicated that NFAT5 was a ubiquitous transcription factor widely expressed in various tissues with pleiotropic functions, such as embryonic development, and cell differentiation ( 11 , 12 ). As an important regulator of both innate and adaptive immunity, NFAT5 is also implicated in the pathogenesis of various diseases, including various inflammatory diseases and cancer development ( 13 18 ).…”
Section: Introductionmentioning
confidence: 99%